2014
DOI: 10.14233/ajchem.2014.18180
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Surfactant-Induced Instantaneous Gelation of Silk Fibroin Solution

Abstract: Modern traumatic wound-care products have several associated disadvantages. They do not meet requirements because they lack good permeability, biocompatibility and air tightness. In an attempt to overcome these shortcomings, a new type of flexible, instantaneouslyformed hydrogels resulting from blending silk fibroin and cationic surfactants with different carbon chains are introduced in this work. The secondary structure of these hydrogels is similar to that of a silk fibroin solution as they primarily consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The addition of SF to the Tween 80-stabilized emulsion also improved the stability of oil droplets, but high-speed centrifugation destroyed the droplet structure, leading to the agglomeration of oil droplets and the formation of SF aggregates (Figure g,h). This change was likely caused by a structural change with the SF and gelation induced by Tween 80, a phenomenon previously described . Furthermore, when the size distribution was examined with the SF-added nSiO 2 -stabilized Pickering emulsion before and after centrifugation, there was no significant difference (∼6 μm, p > 0.05) in the size of oil droplets (inset in Figure c,d,g,h), confirming the conclusion that the combination of SF/nSiO 2 significantly improved the stability of the oil droplets, likely by forming stable shells at the oil/water interface.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The addition of SF to the Tween 80-stabilized emulsion also improved the stability of oil droplets, but high-speed centrifugation destroyed the droplet structure, leading to the agglomeration of oil droplets and the formation of SF aggregates (Figure g,h). This change was likely caused by a structural change with the SF and gelation induced by Tween 80, a phenomenon previously described . Furthermore, when the size distribution was examined with the SF-added nSiO 2 -stabilized Pickering emulsion before and after centrifugation, there was no significant difference (∼6 μm, p > 0.05) in the size of oil droplets (inset in Figure c,d,g,h), confirming the conclusion that the combination of SF/nSiO 2 significantly improved the stability of the oil droplets, likely by forming stable shells at the oil/water interface.…”
Section: Resultssupporting
confidence: 79%
“…This change was likely caused by a structural change with the SF and gelation induced by Tween 80, a phenomenon previously described. 50 Furthermore, when the size distribution was examined with the SF-added nSiO 2stabilized Pickering emulsion before and after centrifugation, there was no significant difference (∼6 μm, p > 0.05) in the size of oil droplets (inset in Figure 1c,d,g,h), confirming the conclusion that the combination of SF/nSiO 2 significantly improved the stability of the oil droplets, likely by forming stable shells at the oil/water interface. It has been known that the coexistence of alternating hydrophobic and hydrophilic domains endows SF with amphiphilic capacity, and stable oil/ SF emulsions have been prepared based on SF 51 and SF nanofibers, 33 which self-assembled at the oil/water interface and lowered surface tension.…”
Section: Resultsmentioning
confidence: 52%
“…Recent studies revealed that the slow dynamics of gelation for a pure SF solution is mainly relevant with conformational transition from random coil to β-sheet structure, which then gradually self-assembles into close-packed β-sheet crystals, acting as a physical cross-link to stabilize SF hydrogel. ,, Although many physical treatment methods (e.g., pH, vortexing, sonication, and electrical field), or the addition of certain organic molecules (e.g., ethanol, surfactants, or hydrophilic polymers), are able to increase the gelation rate of SF by adjusting protein chain–chain interactions, the gelation process induced by instrumental parameters may not be compatible with certain clinical environments, and potential toxicity of certain organic molecules can raise a significant concern for biomedical applications. Thus, searching for a simple and biocompatible way to trigger the gelation of SF is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the role of negatively charged surfactants in inducing SF gelation, the effects of non-ionic and cationic surfactants were also evaluated [100,101]. The chemical structures of the surfactants were illustrated in Figure 11.…”
Section: Figure 10 Chemical Structure Of Sos Sds and Stsmentioning
confidence: 99%